Study the durability of welding and performance of base metal of L. P. G. home cylindrical manufactured in Kurdistan region. - Yassin Mustafa Ahmed; Hameed D. Lafta; Azhin Abdullah Abdulrahman (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2019)
Liquefied petroleum gas (propane or butane) is a colorless liquid which readily evaporates into a gas. It has no smell, although it will normally have an odor added to help detect leaks. Liquefied petroleum gas is stored and handled as a liquid when under pressure inside an LPG cylinder. Liquefied petroleum gas cylinders are subjected to various tests to ensure their compliance requirements as per standard. This research studies the durability of welding and performance of base metal of L. P. G. home cylindrical in Kurdistan region. The experiments were carried out on three types of LPG cylinder using in Kurdistan regions A, B, and C and an unformed plate. To carried out the samples and tests during the research we depending on the standard tests for LPG cylinders. Three samples are extracted from each of LPG cylinders and unformed plate for each of tensile test, Bending test and Hardness test according to ISO 6892-2016 and ASME standards from each type of LPG cylinders and from unformed plate to examine the mechanical properties. In addition, chemical compositions also were carried out. These values are compared with standard.